Myricitrin versus EGCG in the Treatment of Obesity: Target Mining and Molecular Mechanism Exploring based on Network Pharmacology - Yin, Peipei; Huang, Jiangping; Yang, Kang; Deng, Chuang; Yang, Lingguang (Current Pharmaceutical Design, 2023)
Background: Myricitrin is a flavonol glycoside possessing beneficial effects on obesity, a rising global health issue that affects millions of people worldwide. However, the involving target and mechanism remain unclear. Objective: In the present study, the anti-obesity targets and molecular mechanisms of Myricitrin, along with another flavanol Epigallocatechin gallate (EGCG), were explored through network pharmacology, bioinformatics, and molecular docking. Methods: The potential targets for Myricitrin and EGCG were obtained from Pharmmaper, SwissTargetPrediction, TargetNet, SEA, Super-PRED, TCMSP, and STICH databases. Meanwhile, DEG targets were retrieved from GEO datasets, and obesity targets were collected from DrugBank, TTD, DisGeNet, OMIM, GeneCards, PharmGKB, and CTD databases. GO and KEGG pathway enrichment analyses were conducted through Metascape online tool. Protein-protein interaction (PPI) networks were also constructed for compound, DEG, and obesity targets to screen the core targets through MCODE analysis. The further screened-out key targets were finally verified through the compound-target-pathway-disease network, mRNA expression level, target-organ correlation, and molecular docking analyses. Results: In total, 538 and 660 targets were identified for Myricitrin and EGCG, respectively, and 725 DEG targets and 1880 obesity targets were retrieved. GO and KEGG analysis revealed that Myricitrin and EGCG targets were enriched in the pathways correlating with obesity, cancer, diabetes, and cardiovascular disease. Furthermore, the intersection core targets for Myricitrin and EGCG function mainly through the regulation of responses to hormones and involving pathways in cancer. Above all, androgen receptor (AR), cyclin D1 (CCND1), early growth response protein 1 (EGR1), and estrogen receptor (ERS1) were identified as key targets in the compound-target-pathway-disease network for both Myricitrin and EGCG, with significant different mRNA expression between weight loss and control groups. Target-organ correlation analysis exhibited that AR and CCND1 showed high expression in adipocytes. Molecular docking also revealed good binding abilities between Myricitrin and EGCG, and all four receptor proteins. Conclusion: The present research integrated network pharmacology and bioinformatics approach to reveal the key targets of Myricitrin and EGCG against obesity. The results provided novel insights into the molecular mechanism of Myricitrin and EGCG in obesity prevention and treatment and laid the foundations for the exploitation of flavonoid-containing herbal resources.
Keywords: anti-obesity